Calibration and verification of DEM parameters of wet-sticky feed raw materials - Fei Peng; Limei Zhang; Zhiqiang Li; Jianming Chen (Scientific Reports, 2023)
Abstract In order to improve the accuracy of the parameters needed in the discrete element method (DEM) simulation process of wet-sticky feed raw materials, the JKR contact model in DEM was used to calibrate and verify the physical parameters of wet-sticky feed raw materials. Firstly, the parameters that have a significant effect on the angle of repose were screened using a Plackett–Burman design, and the screened parameters were: MM rolling friction coefficient, MM static friction coefficient, and JKR surface energy. Then, the three screened parameters were selected as the influencing factors and the accumulation angle of repose was selected as evaluating indicator; thus, the performance optimization experiments were carried out with the quadratic orthogonal rotation design. Taking the experimentally measured angle of repose value of 54.25°as the target value, the significance parameters were optimized, and the optimal combination was obtained : MM rolling friction factor was 0.21, MM static friction factor was 0.51, and JKR surface energy was 0.65. Finally, the angle of repose and SPP tests were compared under the calibrated parameters. The results showed that the relative error of experimental and simulated tests in angle of repose was 0.57%, and the compression displacement and compression ratio of the experimental and simulated tests in SPP were 1.01% and 0.95%, respectively, which improved the reliability of the simulated results. The research findings provide a reference basis for simulation study and optimal design of related equipment for feed raw materials.